Characterizing the mechanical properties of Multi-Layered CNTs reinforced SBS modified Asphalt-Binder. (16th August 2021) - Zhang, Xiaorui; Zhou, Xinxing; Ji, Wei; Zhang, Fan; Otto, Frédéric
Highlights: MCNTs can potentially improve the elastic properties of SBSMA whilst simultaneously inhibiting the compressibility characteristics. The intermolecular forces between the saturates, aromatics, and SBS were found to be the key ingredients for modifying and reinforcing SBSMA with MCNTs. MCNTs can enhance the crosslinking between the SBS modifier and the asphalt-binder, improve the asphalt-binder polar component distribution, and form a new colloidal system. Abstract: Due to their superior characteristic properties, multi-layered carbon nanotubes (MCNTs) make ideal candidates for use as reinforcing materials, modifiers, or enhancers in asphalt-binders. With this background, this study was conducted to improve the mechanical properties of styrene–butadienestyrene (SBS) modified asphalt-binder (denoted as SBSMA) through injection of various MCNTs dosages into the SBSMA matrix. In the study, molecular dynamic simulations were used to model and quantify the elastic properties (i.e., bulk, shear modulus, etc.) of SBSMA as a function of MCNTs content. The mechanical response curves of the MCNTs reinforced SBSMA, denoted as MSBSMA, were evaluated using the atomic force microscope (AFM) device. The MSBSMA's rheological properties (i.e., complex modulus and phase angle) were measured using the dynamic shear rheometer (DSR) test device. The corresponding results indicated that MCNTs had a profound impact on enhancing both the rheological properties and mechanical response-behavior of MSBSMA. Furthermore, the molecular simulations were found to be satisfactorily comparable to the laboratory experimentation results. Overall, the study findings substantiated that MCNTs can potentially be used to reinforce and enhance SBSMA.